Aplikasi Serat Kapuk dan Balsa dengan Perlakuan Alkali sebagai Bahan Penguat Komposit (Alkaline Treated-Kapok and Balsa Fibers for Composite Reinforcement) - Renny Purnawati; Fauzi Febrianto; Nyoman J Wistara; Siti Nikmatin; Sudirman Sudirman; Marwanto Marwanto (Masyarakat Peneliti Kayu Indonesia, 2018)
Natural fibers of kapok and balsa can be potential renewable raw material for reinforced polymer composite. Alkaline treatment carried out in the present works was intended to develop the physical and chemical properties of the fibers before its application in reinforced composites preparation. The treatments involve of using NaOH at the concentration of 2, 4, 6, 8 and 10%. The change of morphological characteristics, crystallinity index, functional groups, and water contact angle were analyzed by using SEM, FTIR, XRD and contact angle analyzer, respectively. Upon alkaline treatments, the fibers were clean, flatten, and the surface tended to be rough. Defibrillation occurred at higher alkaline concentration. Alkaline treatment on the fibers shifted and changed the peak absorption intensity of -OH, C-O, C=C and C=O. Up to 8% NaOH concentration, alkaline treatment increased the crystallinity of the fibers, however decreased when the concentration of NaOH reaching 10%. Alkaline treatment on the fibers removed lignin, hemicellulose, and waxy substance of the fiber surface, increased surface roughness, and therefore is expected to create better interfacial adhesion.